Science as a “reality show”: the mindset of academic research : La ciencia como “reality show”: la mentalidad de la investigación académica - Norely Margarita Soto Builes, Pedro Alejandro Jurado Castaño, Nora Margarita Vargas Zuluaga (Revista de Orientación Educacional, 2019)
Abstract: This article presents the results from a qualitative research oriented towards analyzing the way the concept of science is understood in universities and how such understanding defines the development of academic research in this area. The results of the research, done under the tenets of the Grounded Theory to university professors, concludes that there has been a transformation in the way research is understood and promote which causes a certain number of tensions and dynamics in the academic environment of social sciences and universities. Resumen: El artículo presenta los resultados de una investigación cualitativa orientada a analizar la forma en que es aprehendido el concepto de ciencia en el escenario universitario y cómo dicha comprensión determina el desarrollo de la investigación académica en ese ámbito. Los resultados de la investigación, realizada bajo los postulados de la teoría fundada, permitieron comprender que se ha producido una transformación en la manera de entender y promover la investigación científica, lo cual causa un determinado número de tensiones y dinámicas en los espacios académicos de las ciencias sociales y las universidades.